\(B=-10-x^2-6x\)
\(\Rightarrow B=-\left(x^2+6x+10\right)\)
\(\Rightarrow B=-\left(x^2+6x+9+1\right)\)
\(\Rightarrow B=-\left[\left(x+3\right)^2+1\right]\)
Vì \(\left(x+3\right)^2\ge0\forall x\)\(\Rightarrow\left(x+3\right)^2+1\ge1\)
\(\Rightarrow-\left[\left(x+3\right)^2+1\right]\le-1\)
=> Đpcm
B=\(-10-x^2-6x\)
B=\(-x^2-6x-9-1\)
B=\(-\left(x^2+6x+9\right)-1\)
=\(-\left(x+3\right)^2-1\)
Ta có : \(\left(x+3\right)^2\ge0\forall x\)
\(-\left(x+3\right)^2\le0\)
\(-\left(x+3\right)^2-1\le-1\)
Vậy B luôn âm với mọi x
Ta có B = -x2 - 6x - 10
= -x2 - 6x - 9 - 1
= -(x + 3)2 - 1 \(\le\) - 1 < 0
=> B < 0 với mọi x
B = -10 - x2 - 6x
B = -x2 - 6x - 9 - 1
B = -( x2 + 6x + 9 ) - 1
B = -( x + 3 )2 - 1 \(\le1< 0\forall x\)( đpcm )